Considerations to improve the safety of cervical spine manual therapy. (February 2018) - Hutting, Nathan; Kerry, Roger; Coppieters, Michel W.; Scholten-Peeters, Gwendolijne G.M.
Abstract: Manipulation and mobilisation of the cervical spine are well established interventions in the management of patients with headache and/or neck pain. However, their benefits are accompanied by potential, yet rare risks in terms of serious adverse events, including neurovascular insult to the brain. A recent international framework for risk assessment and management offers directions in the mitigation of this risk by facilitating sound clinical reasoning. The aim of this article is to critically reflect on and summarize the current knowledge about cervical spine manual therapy and to provide guidance for clinical reasoning for cervical spine manual therapy. Highlights: Prevention of potential serious adverse events is important in manual therapy. Identifying a possible vasculogenic origin or other serious pathology is important. Indications, contraindications and risk factors for manual therapy must be assessed. Patient interviewing, clinical assessment, interpretation and analysis are important skills.